Chemoenzymatic Platform for Synthesis of Chiral Organofluorines Based on Type II Aldolases. Issue 34 (19th July 2019) - Fang, Jason; Hait, Diptarka; Head‐Gordon, Martin; Chang, Michelle C. Y.
Abstract: Aldolases are C−C bond forming enzymes that have become prominent tools for sustainable synthesis of complex synthons. However, enzymatic methods of fluorine incorporation into such compounds are lacking due to the rarity of fluorine in nature. Recently, the use of fluoropyruvate as a non‐native aldolase substrate has arisen as a solution. Here, we report that the type II HpcH aldolases efficiently catalyze fluoropyruvate addition to diverse aldehydes, with exclusive (3 S )‐selectivity at fluorine that is rationalized by DFT calculations on a mechanistic model. We also measure the kinetic parameters of aldol addition and demonstrate engineering of the hydroxyl group stereoselectivity. Our aldolase collection is then employed in the chemoenzymatic synthesis of novel fluoroacids and ester derivatives in high stereopurity (d.r. 80–98 %). The compounds made available by this method serve as precursors to fluorinated analogs of sugars, amino acids, and other valuable chiral building blocks. Abstract : Pyruvate aldolases of the type II HpcH family are excellent catalysts for fluoropyruvate addition to aldehydes. The stereoselectivity and kinetic behavior are rationalized, and engineering of hydroxyl stereoselectivity is demonstrated. Downstream reactions allow the synthesis of numerous fluorinated analogs of sugars, amino acids, and other valuable chiral organofluorines.